Copper(I)-Catalysed Deacetylenative Cross-Coupling Reaction of Terminal Alkynes with Propargylic Amines via C(sp)–C(sp3) Bond Cleavage - Kim, Yongeun; Nakamura, Hiroyuki (Synlett, 2012)
The catalytic deacetylenative coupling reaction of terminal alkynes with various N-substituted propargylic amines proceeded in the presence of CuCl (10 mol%) and Na2HPO4 (4 equiv) in THF at 130 °C to give the corresponding substituted propargylic amines in good to high yields.
Keywords: alkynes; amines; copper; cleavage; catalysis